1984
DOI: 10.1021/ja00338a070
|View full text |Cite
|
Sign up to set email alerts
|

Neither the retinal ring nor the ring double bond is required for proton pumping in bacteriorhodopsin: acyclic retinal bacterioopsin analogs

Abstract: Die 2‐cis‐ und all‐trans‐Isomere der acyclischen Retinale (I) bilden mit Bacterioopsin Pigmente, die gegenüber Hydroxylamin empfindlich sind, bei 4°C Lichtadaption zeigen und als dunkeladaptienes Pigment den 2‐cis‐ und all‐trans‐ bzw. den all‐trans‐Chromophor enthalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
9
1

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 1 publication
4
9
1
Order By: Relevance
“…This reconstitution behavior is similar to that of BR apoprotein with ring desmethyl analogues (Gartner et al, 1983;Courtin et al, 1987) and acyclic retinal analogues (J. Rao et al, 1985;Crouch et al, 1984) but differs from the behavior of bovine opsin (Crouch and Or, 1983) whose regenerability is sensitive to ring modifications (Kropf et al, 1973). The absorption maxima of SR-I analogues are shifted to longer wavelengths compared with those of corresponding model protonated Schiff bases measured as previously reported (Arnaboldi et al, 1979) (Table 1).…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…This reconstitution behavior is similar to that of BR apoprotein with ring desmethyl analogues (Gartner et al, 1983;Courtin et al, 1987) and acyclic retinal analogues (J. Rao et al, 1985;Crouch et al, 1984) but differs from the behavior of bovine opsin (Crouch and Or, 1983) whose regenerability is sensitive to ring modifications (Kropf et al, 1973). The absorption maxima of SR-I analogues are shifted to longer wavelengths compared with those of corresponding model protonated Schiff bases measured as previously reported (Arnaboldi et al, 1979) (Table 1).…”
Section: Resultssupporting
confidence: 69%
“…Studies with modified conjugated systems and fl-ionone ring/ polyene chain conformations (Baselt et al, 1989) have shown that the steric and electrostatic properties of the retinal binding sites in SR-I and BR have been conserved despite their different functions. Ring-modified retinal analogues have been used to study the role of the ,3-ionone ring in BR and rhodopsin (Gartner et al, 1983;Courtin et al, 1987;Crouch and Or, 1983;Crouch et al, 1984;Kropf et al, 1973). These studies showed specific interactions between ring methyls and the protein binding site are essential for bovine rhodopsin but not for BR to form stable pigments, and that BR proton pumping is not sensitive to ring portion modifications.…”
Section: Introductionmentioning
confidence: 99%
“…The chromophore binding site of bacteriorhodopsin is specific for the all-trans and 13-cis isomers of retinal (1) (Kohl & Sperling, 1979). We have previously shown that the cyclohexyl ring of retinal is not required for pigment formation, as acyclic retináis such as 2-4 can form stable pigments with bacterioopsin (Crouch et al, 1984). These results are in agreement with experiments showing that bacterioopsin does not have a specific cyclohexyl ring binding site (Towner et al, 1981).…”
supporting
confidence: 88%
“…We could not detect any pigment formation with all‐ trans phenyl retinal (PHE). The lack of a stable AR3:PHE pigment indicates that this analog cannot be stably contained in the retinal binding pocket of AR3, most probably due to the absence of methyl groups on the phenyl ring, which strongly contribute to correct positioning and stabilization in the retinal binding pocket . This mirrors results obtained with GR, which does not appear to bind PHE, and is in contrast to PR, which forms a stable blueshifted PHE pigment .…”
Section: Resultssupporting
confidence: 60%